Efforts to increase knowledge of mother toddlers about complementary foods to breastfeeding in Mapane Village, Poso, Indonesia - Nuraidah, Ida; Noya, Fransisca; Siregar, Nilda Yulita; Sitorus, Sony Bernike Magdalena; Entoh, Christina (Community Empowerment, 2021)
The nutritional needs of infants 6-24 months can be met by providing complementary foods with breast milk (MP-ASI). One of the causes of the increasing incidence of malnutrition at 12 to 24 months of age in the world and in Indonesia is the provision of complementary foods that are not in accordance with WHO standards. The purpose of this activity is to increase the knowledge of mothers about complementary foods. This activity was held in Mapane Village on November 7, 2020. The target of this activity is 5 mothers of toddlers. The method of this activity was distributing pre-test questionnaires to participants, distributing leaflets then conducting counseling, and evaluating activities through post-tests. The results of the counseling obtained an increase in the knowledge of mothers under five about complementary foods. The average of knowledge before extension was 74% and the average after extension was 96%. The results of this service recommend that village midwives in Mapane Village be able to provide continuous counseling at each posyandu